Os problemas da sublimação: o objeto entre a idealização e a Coisa - George Avance Pereira Ramos (2009)
This works purpose is to present a profound study in the concept of sublimation, emphasizing the moments in which the psychoanalitc theory has found some paradoxes. Beetwen several concepts of psychoanalisis, idealization has been chosen as a counterpoint to sublimation, for this debate presents a few important advances in concern to the psychanalitic conceptions of desire, drive and object. This study, therefore, has passed in first instance by many points in the theorization on the objects of desire and drive. Then, it has turned to the ways of the costruction of ideals, Ideal Ego and Ego Ideal, i.e. the ways of the idealization. At last, we developed a thorough examination of the sublimations theme, taken from what Lacan has called the paradigm of sublimation, i.e. the main function of das Ding, recovered by Lacanfrom the Freudian text, in its close relationship with idealization and the special place occupied by the idealizaton in the Courtly Love.